The Poisson-exponential distribution: a Bayesian approach - Louzada-Neto, Francisco; Cancho, Vicente G.; Barriga, Gladys Dorotea Cacsire [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2011)
In this paper, we proposed a new two-parameter lifetime distribution with increasing failure rate. The new distribution arises on a latent complementary risk scenario. The properties of the proposed distribution are discussed, including a formal proof of its density function and an explicit algebraic formulae for its quantiles and survival and hazard functions. Also, we have discussed inference aspects of the model proposed via Bayesian inference by using Markov chain Monte Carlo simulation. A simulation study investigates the frequentist properties of the proposed estimators obtained under the assumptions of non-informative priors. Further, some discussions on models selection criteria are given. The developed methodology is illustrated on a real data set.
Keywords: Bayesian inference; complementary risks; exponential distribution; Poisson distribution; survival analysis